The Effectiveness of Group Counselling with Cognitive Restructuring and Self-Management Techniques to Reduce Internet Addiction - Fadil, M; Sunawan, Sunawan; Awalya, Awalya (Jurnal Bimbingan Konseling, 2019)
This study aimed to examine the effectiveness of group counseling with Cognitive Restructuring and Self-management techniques to reduce internet addiction. For more, the study used experimental method with pre-test – post-test one group design through Mixed Anova model. This involved 14 students of Public Vocational High School 12 Surabaya (SMKN 12 Surabaya) as research subjects chosen by using purposive sampling technique. Based on Mixed Anova analysis, it was known that group counseling with Cognitive Restructuring and Self-management techniques was effective to reduce students’ internet addiction. These findings asserted that students who received group counseling with Cognitive Restructuring and Self-management techniques experienced internet addiction reduction.